2016
DOI: 10.1007/s00268-016-3496-z
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Intramedullary Nailing for Femoral Shaft Fractures in Dar es Salaam, Tanzania

Abstract: Background Femoral shaft fractures are one of the most common injuries seen by surgeons in low-and middleincome countries (LMICs). Surgical repair in LMICs is often dismissed as not being cost-effective or unsafe, though little evidence exists to support this notion. Therefore, the goal of this study is to determine the cost of intramedullary nailing of femoral shaft fractures in Tanzania. Methods We used micro-costing methods to estimate the fixed and variable costs of intramedullary nailing of femoral shaft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…Previous studies at the same institution in Tanzania have shown that femoral nailing with the same SIGN IM nail is a more cost-effective treatment compared to traction based on cost of treatment, as have studies using the same nail in Kenya and Cambodia [3, 12, 13]. While at a different anatomic location, our results support these studies in the use of IMN as a cost effective surgical management modality that should not be hindered by limited availability.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies at the same institution in Tanzania have shown that femoral nailing with the same SIGN IM nail is a more cost-effective treatment compared to traction based on cost of treatment, as have studies using the same nail in Kenya and Cambodia [3, 12, 13]. While at a different anatomic location, our results support these studies in the use of IMN as a cost effective surgical management modality that should not be hindered by limited availability.…”
Section: Discussionsupporting
confidence: 83%
“…Granted that increased risk of infection with use of internal fixation as a first line treatment in open fractures may be one reason for this practice, the other major reason is unavailability of implants which are prohibitively expensive 39,40 ; even closed fractures requiring surgical fixation are commonly managed conservatively for this reason. 14,41 This study reveals that surgical debridement plus conservative treatment (US$1177) is in fact more costly than ORIF (US$618) as a result of this prolonged ward stay. Although the ORIF cost here excludes the cost of implants (about US$134 14 ), since they were not captured in the routine hospital cost records, it includes the costs of prolonged preoperative clinic visits.…”
Section: Discussionmentioning
confidence: 90%
“…14,41 This study reveals that surgical debridement plus conservative treatment (US$1177) is in fact more costly than ORIF (US$618) as a result of this prolonged ward stay. Although the ORIF cost here excludes the cost of implants (about US$134 14 ), since they were not captured in the routine hospital cost records, it includes the costs of prolonged preoperative clinic visits. Indeed, cost-effectiveness studies in Kenya 42 and the United States 43 had demonstrated that internal fixation offers better clinical outcomes at lower costs compared to non-operative fixation of fractures.…”
Section: Discussionmentioning
confidence: 90%
“…A large prospective cohort study was recently completed in Tanzania demonstrating that surgical treatment is safe and effective when performed with intramedullary implants rather than plates and screws (29). Secondary studies have also demonstrated the potential cost savings associated with access to efficient surgical treatment and relatively poor outcomes with skeletal traction (30, 31). A multicenter study is currently ongoing in Malawi to establish the cost-effectiveness of surgical treatment compared to skeletal traction.…”
Section: Methodological Aspectsmentioning
confidence: 99%